Pattern of Biomass Accumulation and Productivity of L. Leucocephala Var. K-8 under Different Spacing - Mishra, C. M.; Srivastava, R. J.; Singh, S. L. (Indian Forester, 1986)
The present study deals with the accumulation pattern of biomass (dry matter) by Leucoma leueocephala var. K-8, under different planting space at Kanpur. It is obvious by the present investigation that biomass accumulation pattern differs in plant part as well as in different spacing with similar deviations in average height and diameter However, the values were found maximum in the spacement of 1.25 Ã—l 25 m2 out of 4 different spacing. Taken for study. The mean annual increment (MAI) was also found maximum i.e. 5307 mt/ha/yr in the same spacing. Hence, along road side the planting distance of 1.25 Ã— 1.25m has been suggested for maximum yield.